Histopathological study of response of Vitis vinifera cv. Cabernet Sauvignon to bark and wood injury with and without inoculation by Phaeomoniella chlamydospora - Jérôme POUZOULET; Alban JACQUES; Xavier BESSON; Jean DAYDE; Nathalie MAILHAC (Phytopathologia Mediterranea, 2013)
Summary. Phaeomoniella chlamydospora (Pch) is one of the main causal agents of tracheomycosis in grapevine. We characterize how this fungus affects the response of Vitis vinifera cv. Cabernet Sauvignon to bark and xylem-tissue wounding after six weeks post-treatment. A histological investigation shows that, in xylem tissue, cell-wall modifications in response to wounding are related to suberin deposits rather than to lignin-induced wall thickening. The xylem response does not appear to be disturbed by Pch infection. Therefore, cell-wall modification strongly inhibits the development of wound-closure tissue (WCT) but does not prevent the differentiation of the necro-phylactic periderm. Hyphae localization in tissue surrounding the wound or inoculation sites indicates that Pch colonizes all cell types, such as vascular tissues, paratracheal parenchyma cells, fibers and rays. The results also suggest that efficient compartmentalization separating fascicular xylem portions is assured by thick suberized cell walls bordering the ray parenchyma.